Sistema informático para la gestión administrativa del departamento de planeamiento de la Universidad Técnica de Cotopaxi. - Gancino Tarco, Viviana Paola (2018)
Currently, educational institutions try to improve the information management processes through different ways, for instance: computer tools, which allow to improve and control the information. This research aim is to improve the processes carried out by the Planning Department through the automatization of the Action Plan and Strategic Monitoring, therefore, it’s established the Scrum Eagle methodology, which allows working collaboratively as a team, obtaining results quickly through the Incremental Iterative model. For the development of the website, tools were used such as: SQL Server 2008, and Visual Studio 2012, which facilitates the correct handling and storage of the information of the department, besides, with the purpose of obtaining wonderful designs to the user’s view, was used Jquery and Bootstrap technology. The result was the management of activities by project, the evaluation according to the activity, comments, corrective actions, completion date, etc. Subsequently, the Strategic Monitoring format is generated, which will allow qualifying the applied projects, in this way, the signaling will automatically be generated according to the assigned rating, finally, improvement actions and possible strategies will be entered.